MENGEMBANGKAN KETERAMPILAN NEGOSIASI UNTUK MENGATASI PERSELISIHAN - Isyara desri Isyara desri (CV Abid Abadi Jaya, 2024)
This study aims to evaluate the effectiveness of psychoeducation on negotiation skills with 20 students from the 11th grade at SMA Negeri 2 Nisam, Aceh Utara. The psychoeducational method was implemented in several phases: preparation, core activities, and closure. The material covered includes definitions of emotions, types of emotions, the concept of conflict, and conflict resolution strategies. The activities lasted 45 minutes for the material presentation and 15 minutes for interactive discussion sessions. The results indicate that the psychoeducation significantly improved students' understanding of negotiation skills, demonstrated through their active participation in discussions and enthusiasm during the Q&A session. Participants also recognized the importance of emotional regulation in resolving peer conflicts without confrontation. The session concluded with the distribution of door prizes and certificates as a form of appreciation. This study emphasizes that the psychoeducational method is effective in enhancing students' awareness and interpersonal skills. The implication of this finding is the importance of integrating similar programs in schools to develop students' negotiation abilities and emotional regulation, fostering more harmonious interpersonal relationships.Negotiation skills are crucial in managing conflicts effectively, especially among adolescents who often face social pressures.